FUNGAL BIODEGRADATION AND EXOGENOUS ENZYME SUPPLEMENTATION OF CASSAVA STARCH RESIDUE FOR BROILER PRODUCTION (2014)
Cassava Starch Residue (CSR) contains insoluble fibrous component that makes it unsuitable for monogastrics. Its digestibility can be enhanced through microbial biodegradation or probiotic-addition which had been used in ruminants feeding. Information on fungal-treated or enzyme-supplemented-CSR and its use as feedstuff for poultry is a contribution to the giving body of knowledge. Thus, fungal biodegradation and exogenous enzyme supplementation of CSR in broiler was investigated. One hundred and eighty a-day old Hybro-chicks were allotted to six treatments (r=6) and fed for 49 days on diets containing CSR of 0(control), 5,10, 15, 20 and 25% for optimal utilisation determination. Feed Conversion Ratio (FCR), Body Weight Gain (BWG g/day), Relative Weights (RW) of gizzard, kidney, liver, and heart were measured. Blood cholesterol (mg/100mL) was determined. Apparent Nutrient Digestibility (AND) of Crude Protein (CP) and Crude Fibre (CF) were evaluated. The CSR was biodegraded with Aspergillus niger, Trichoderma viride and their mixtures (ratio 1:3, w/w) for 0, 7, 14 and 21 days using solid state fermentation procedure for screening. Ether Extract(EE), CP, CF, Acid Detergent Fibre (ADF), Neutral Detergent Fibre(NDF), and Acid Detergent Lignin (ADL) of biodegraded-CSR were determined. Furthermore, 180 a-dayold chicks were randomly alloted to groups (n=36) and fed diets containing 0, 5, 10, 15, 20 and 25% of A. niger biodegraded-CSR for 49 days. Pure enzymes (Roxazyme G2G and cellulase) were added to CSR each at 10, 20 and 30% and fed to 210 1-day old chicks (n=42) for 49 days. FCR, BWG, RW; AND: CP, CF, EE, ADF, NDF, ADL, total protein and blood cholesterol were assessed. Data were analysed using the descriptive statistics and ANOVA of completely randomized design at α0.05.The FCR and BWG of birds fed 5% CSR were 2.01±0.01 and 41.0±0.15, and at 0% CSR were 2.10±0.03 and 38.50±0.16 respectively. The RW of gizzard and liver were significantly higher in birds fed CSR compared with control. Blood cholesterol decreased significantly from 148.9±10.5 mg/100mL in control birds to 93.90±6.6 mg/100mL compared to birds fed 25% CSR , while AND of CP and CF were similar in CSR diets. Biodegradation increased CP of CSR by 72.8±0.31% and decreased CF by 33.9±0.09% after 14days. Aspergillus niger decreased the NDF from 68.0±0.28% to 53.7±0.16%, ADF 32.0±0.13% to 20.6±0.09%, and ADL 14.9±0.31% to 12.4±0.12% in CSR than T. viride and mixture of A. niger and T. viride. The FCR (1.94±0.02) and BWG (46.4±0.17) of birds fed 15% biodegraded-CSR was different when compared with 0% biodegraded-CSR. Addition of Roxazyme G2G or Cellulase each with 20% CSR diet improved FCR (1.89±0.01, 1.91±0.04) and BWG (47.2±0.12, 47.1±0.20) respectively compared with control. However, RW and AND of CP, CF, EE, NDF and ADF improved in birds fed A. niger-biodegraded and enzyme supplemented diets. Total serum proteins and blood cholesterol levels were however not affected. Fungal biodegraded at 15% and enzyme supplemented at 20% cassava starch residue enhanced performance of broilers and also lowered the blood cholesterol